Mulher e consumidora com deficiência: um em estudo sobre autoaceitação de agregação identitária no contexto do vestuário - Pontes, Bruna Maria Pereira de (2023)
Becoming a person with a disability involves several transformations, from physical to emotional, which are influenced by identity, personal, cultural, and social aspects. Acquiring a disability presents itself as a turning point and the individual needs to learn how to deal with their new body and its limitations. Thus, their roles are also changed and one more identity needs to be assumed, that is, a person with a disability. In this context, the general objective of this dissertation is to understand how women consume clothes after becoming a person with a disability and how the process of self-acceptance of this identity aggregation occurs. To make the study possible, secondary guiding questions were elaborated: (i) How does the process of aggregating a new identity after a traumatic event occur? (ii) What are the changes that occur in clothing consumption during the process of self-acceptance of another identity? (iii) How do women with physical disabilities acquire clothing? For this, a qualitative approach was adopted, whose data collection took place in two ways: non-participant observation on Instagram and life history interviews were conducted with women who started to present physical disability at the interval of at least two years. Data analysis followed the steps of narrative analysis. The findings attest that the process of self-acceptance or identity aggregation is continuous and complex. It depends on temporal comparisons, on how other people see themselves as participants, and whether there are phases of greater acceptance or less acceptance throughout life. In addition, the results discuss how the participants have their consumption abilities disregarded by unfulfilling their demands in the clothing and footwear sector. It is clear, therefore, that this research presents advances in the body of knowledge, by bringing light to another context experienced by people with disabilities. The study also develops the theme by using other theoretical frameworks, such as the theory of subjective change. In addition, it reverberates to a frequent social problem, such as people with disabilities as vulnerable consumers.